2011
DOI: 10.1001/jama.2011.879
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and Prostate Cancer Survival and Recurrence

Abstract: Context Studies of smoking in relation to prostate cancer mortality or recurrence in prostate cancer patients are limited, with few prostate cancer-specific outcomes. Objective To assess the relation of cigarette smoking and smoking cessation with overall, prostate cancer-specific, and CVD mortality and biochemical recurrence among men with prostate cancer. Design, Setting, and Participants Prospective observational study of 5 366 men diagnosed with prostate cancer between 1986–2006 in the Health Professio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
190
3
12

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(215 citation statements)
references
References 41 publications
10
190
3
12
Order By: Relevance
“…Many studies have shown a significant and consistent association between smoking and increased mortality from prostate cancer [1][2][3][4][5][6]. These studies differed in how they defined smokers and their risk after ceasing to smoke.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown a significant and consistent association between smoking and increased mortality from prostate cancer [1][2][3][4][5][6]. These studies differed in how they defined smokers and their risk after ceasing to smoke.…”
Section: Discussionmentioning
confidence: 99%
“…While incident studies have been inconsistent, mortality studies have consistently shown a significant correlation between cigarette smoking and increased mortality from prostate cancer [1][2][3][4][5][6][7]. Given the prevalence of smoking in the USA (the Centers for Disease Control and Prevention reported that, as of 2010, 19.3% of USA adults were current smokers) and the prevalence of prostate cancer, there is a need to determine if smoking negatively influences the success of local therapy.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies have consistently shown that current smokers have an increased risk of fatal prostate cancer. 27,29 Delayed detection of prostate cancer due to the effects of smoking on PSA may contribute in part to worse health outcomes of prostate cancer among smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Men who perform moderate amounts of exercise weekly have been shown to have lower risk of prostate cancer diagnosis, as well as risk of high-grade disease [37]. Additionally, tobacco smoking at the time of prostate cancer diagnosis is associated with increased prostate-cancer-specific mortality, as well as biochemical recurrence, after adjusting for stage, grade, and PSA screening history [38]. Men with male factor infertility have been found to have increased risk of prostate cancer [39].…”
Section: Who Is At Risk?mentioning
confidence: 99%